Ethnocentrism, Localization Success, and Cultural Intelligence: Mediating Role of Knowledge Sharing in Digital Marketing: Ethnocentric Behaviour in Digital Marketing - Violinda, Qristin; Kurniawan, Bayu; Indiworo, Hawik Ervina; Fathurachman, Chadyan; Khaydarov, Alisher (Journal of Digital Marketing and Halal Industry, 2025)
Ethnocentric behavior among employees is observed in multicultural work environments characterized by the presence of individuals from different origins. The presence of ethnocentrism in the workplace has been observed to have an impact on coworkers. However, despite the importance of the above-mentioned factors, there has been no relevant scientific study on how these aspects affect human resource localization. This study investigates the influence of ethnocentric behavior and localization success on cultural intelligence through the mediating role of knowledge sharing tendency in the context of digital marketing. Although prior research has examined ethnocentrism in consumer behavior and policy, there is limited understanding of how individual-level ethnocentric tendencies affect human resource localization and intercultural competence in multinational work environments. Addressing this gap, the study surveyed 107 employees in multinational companies in Indonesia using a non-probability snowball sampling method. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. The findings show that ethnocentric behavior and localization success positively influence both knowledge sharing tendency and cultural intelligence. However, knowledge sharing tendency does not significantly mediate the relationship between either ethnocentric behavior or localization success and cultural intelligence. These results highlight the importance of direct cross-cultural dynamics in enhancing cultural intelligence. The study contributes to the theoretical development of international HR management and cultural adaptation models while offering practical implications for designing training programs and policies that enhance knowledge transfer and cultural intelligence in global digital marketing environments.